High dose epinephrine in the management of life-threatening hypotension from post-surgical hemorrhage with an excellent outcome in a patient with Phaeochromocytoma: A case report - Arul James; Gavin Robertson; Neil Bhardwaj; David Lloyd; G Niraj (Journal of Surgery and Surgical Research - Peertechz Publications, 2022)
Epinephrine is widely used in the management of severe cardiovascular instability as well as in cardiac arrest. In cardiac arrest, epinephrine has a standard dose (1mg) given at fixed intervals. We present a report on the use of high dose epinephrine (35mg in 45 minutes) during the successful management of a patient with sustained profound hypotension as a result of massive hemorrhage following laparoscopic adrenalectomy.